Stroke and atrial fibrillation: An update - Nicole Beaton Sur; Jose G. Romano (Revista Mexicana de Neurociencia, 2022)
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia encountered in clinical practice. AF is associated with an increased risk of cardiovascular disease, heart failure, stroke, cognitive impairment and dementia, and mortality. Individuals with AF have a 5-fold risk of ischemic stroke, and AF-related strokes are associated with greater disability and mortality compared with strokes from other causes. Moreover, the burden of AF and AF-related stroke on patients, their caregivers, health-care systems, and society is significant and projected to increase in the coming decades due to the rapid growth of the ageing population. The care and management of patients with AF and AF-related stroke are challenging, often involving complex decision-making to weigh the risks and benefits of various treatment and prevention strategies. This topical review focuses on the latest science and advances in AF and AF-related stroke and identifies knowledge gaps and future directions of continued research.